Mecanismos de regeneração natural em remanescente de Floresta Estacional Decidual - Marta Silvana Volpato Sccoti; Maristela Machado Araujo; Cristiane Friedrich Wendler; Solon Jonas Longhi (Ciência Florestal, 2011)
Due to the loss of biodiversity and natural habitat because of the forests fragmentation, it is the needed to find alternatives that allow the recovery of these environments. Thus, this study aimed to obtain information about the potential of natural regeneration mechanisms (seed rain, soil seed bank, seedling bank and established natural regeneration) in a seasonal deciduous forest fragment in Santa Maria - RS state, in order to conserve and to recover these ecosystems. The study was conducted in a systematic way, having as a point of departure the demarcation of 14 sampling plots of 2000 sq m. From those plots, 70 subplots were randomly selected to evaluate the natural regeneration mechanisms. The seed rain was evaluated during one year based on the material that was monthly collected and analyzed from the collectors. To the study of the soil seed bank, soil samplings of 25cmx25cmx5cm were taken and the collected material was monitored during 7 months, observing the seed germination. The natural regeneration was evaluated in two classes: seedling bank and established natural regeneration, where individuals h > 30 cm and DBH < 5 cm were identified and measured. The seed rain presented medium density of 1350 seeds m-², in which 73 species, predominantly arboreal, were observed. In the soil seed bank, 108 species were observed, in which 74 % were herbaceous. In the seedling bank, 48 species were found and they we re heliophilousand sciaphilous species, while in the established natural regeneration, 37 species were found, prevailing sciaphilous. This study concluded that the species with the greatest potential to perpetuate in the tudied area were Gymnanthes concolor, Soroceae bonplandii, Eugenia rostrifolia, Trichilia claussenii, Trichilia elegans and Dasyphylum spinescens, and they are highly indicated to the enrichment of the area. The species Myrocarpus frondosus, Cupania vernalis, Nectandra megapotamica and Syagrus rommanzoffiana showed certain restriction, depending on the silvicultural treatments in the forest to assure their perpetuation in the area.